Clinical outcomes of laser in situ keratomileusis with an aberration-neutral profile centered on the corneal vertex comparing vector planning with manifest refraction planning for the treatment of myopic astigmatism - Arbelaez, Maria Clara; Verma, Shwetabh (Journal of cataract and refractive surgery, 2018)
PURPOSE: To evaluate clinical outcomes of laser in situ keratomileusis (LASIK) with an aberration-neutral profile centered on the estimated visual axis (considering 70% of the pupil offset toward the corneal vertex) comparing vector planning with manifest refraction planning for the treatment of myopic astigmatism. SETTING: Muscat Eye Laser Center, Muscat, Sultanate of Oman, Muscat, Oman. DESIGN: Retrospective case series. METHODS: The outcomes were evaluated at a 6-month follow-up in eyes showing ocular residual astigmatism (ORA) over 0.75 diopters (D) preoperatively. RESULTS: Eighty-five treatments were based on manifest astigmatism (preoperative sphere -2.11 D ± 1.3 [SD], cylinder -0.90 ± 1.0 D), and 79 treatments were based on vector planning (preoperative sphere -2.46 ± 1.5 D, cylinder -0.78 ± 0.79 D). At a 6-month follow-up, 128 patients (164 eyes) were evaluated and no significant differences were observed between the 2 groups in terms of difference between corrected distance visual acuity and uncorrected distance visual acuity (UDVA) (P = .1, t test and Fisher exact test Snellen lines 1 or better, P = .4) and postoperative UDVA (P = .05, t test and Fisher exact test for UDVA 20/16 or better, P = .3). Significant differences were observed between the 2 groups in terms of achieved spherical equivalent (P = .04), corneal toricity, and ORA (P < .001, t test and Fisher exact test for ORA ≤0.75 D, P < .001). CONCLUSION: Performing LASIK for myopic astigmatism with the vector planning approach resulted in comparable visual outcomes to manifest refraction planning.